Luther and the Law in the Lutheran Church of Uganda - Ekyarikunda, Enoch; Eck, Ernest van (2016)
This article investigates the role of the Law in the Lutheran Church of Uganda. It investigates how the Law is understood and lived among Lutherans in Uganda. Luther, the sixteenthcentury Reformer, understood and interpreted the Law in terms of the social and cultural context of his time. Luther’s background is very different and so much removed from the African context in which the Ugandan Lutherans find themselves today. Therefore, can the Lutheran Church of Uganda have the same understanding and interpretation of the Law as the Reformer? Is Luther’s sixteenth-century European understanding of the Law applicable to the current Lutherans in Africa, specifically in the Lutheran Church of Uganda? This article examines the social and cultural context of Lutherans in Uganda and determines how it affects their understanding and interpretation of the Law. The article aims to demonstrate that the social and cultural context of the people plays an important role in the way the Christian life is conducted. This article appeals to Paul’s situation in Galatians to prove this point.
Keywords: Sociology and Ethics; Ancient Semitic and Classical Languages; Philosophy; Aspects of Religious Studies; Practical Theology; Ministers of Religion; Scholars; Philosophers; Theologians; Netherdutch Reformed Church; Theology